Predictive Value of Helix Pomatia Agglutinin (HPA) Lectin in Management of Complete Hydatidiform Mole - Ziba Shokri; Fatemeh Atabaki Pasdar; Haleh Ayatollahi; Siamak Naji; Gholam Hossein Farjah (Journal of Clinical and Basic Research, 2018)
Background and objectives: Hydatidiform mole is the most common form of gestational trophoblastic disease, which originates from the placenta and is categorized into complete and partial hydatidiform moles. About 10-30% of complete hydatidiform moles (CHMs) might develop into persistent trophoblastic disease. Helix pomatia agglutinin (HPA) lectin has been suggested as a marker of alteration of glycosylation in human malignancies. The aim of this study was to determine efficacy of HPA lectin as a prognostic indicator for clinical behavior of CHMs. Methods: Lectin histochemistry with biotin-conjugated HPA lectin was performed on paraffin sections of CHM tissues from 24 patients with progression to persistent trophoblastic disease (case group) and 24 patients with spontaneous regression (control group). The sections were graded according to lectin staining intensity (0-3) and the percentage of cell reactions was evaluated based on the staining grades. Results: HPA lectin showed a mild to moderate reactivity with syncytiotrophoblasts, which was most evident in apical portion, but did not react with cytotrophoblasts and stromal cells. The mean staining intensity values did not differ significantly between the two groups (P=0.447). Conclusion: Based on the results, HPA lectin is not a good prognostic indicator for clinical behavior of CHMs.